Defective Autophagy in Vascular Smooth Muscle Cells Alters Vascular Reactivity of the Mouse Femoral Artery - De Munck, Dorien G.; De Moudt, Sofie; Roth, Lynn; De Meyer, Guido R. Y.; Martinet, Wim; Fransen, Paul (Frontiers in Physiology, 2020)
Autophagy is an important cellular survival process that enables degradation and recycling of defective organelles and proteins to maintain cellular homeostasis. Hence, defective autophagy plays a role in many age-associated diseases, such as atherosclerosis, arterial stiffening and hypertension. Recently, we showed in mice that autophagy in vascular smooth muscle cells (VSMCs) of large elastic arteries such as the aorta is important for Ca2+ mobilization and vascular reactivity. Whether autophagy plays a role in the smaller muscular arteries, such as the femoral artery, and thereby contributes to for example, blood pressure regulation is currently unknown. Therefore, we determined vascular reactivity of femoral artery segments of mice containing a VSMC specific deletion of the essential autophagy gene Atg7 (Atg7F/F SM22α-Cre+) and compared them to femoral artery segments of corresponding control mice (Atg7+/+ SM22α-Cre+). Our results indicate that similar to the aorta, femoral artery segments showed enhanced contractility. Specifically, femoral artery segments of Atg7F/F SM22α-Cre+ mice showed an increase in phasic phenylephrine (PE) induced contractions , together with an enhanced sensitivity to depolarization induced contractions. In addition, and importantly, VSMC sensitivity to exogenous nitric oxide (NO) was significantly increased in femoral artery segments of Atg7F/F SM22α-Cre+ mice. Notwithstanding the fact that small artery contractility is a significant pathophysiological determinant for the development of hypertension, 7 days of treatment with angiotensin II (AngII), which increased systolic blood pressure in control mice, was ineffective in Atg7F/F SM22α-Cre+ mice. It is likely that this was due to the increased sensitivity of VSMCs to NO in the femoral artery, although changes in the heart upon AngII treatment were also present, which could also be (partially) accountable for the lack of an AngII-induced rise in blood pressure in Atg7F/F SM22α-Cre+ mice. Overall, our study indicates that apart from previously shown effects on large elastic arteries, VSMC autophagy also plays a pivotal role in the regulation of the contractile and relaxing properties of the smaller muscular arteries. This may suggest a role for autophagy in vascular pathologies, such as hypertension and arterial stiffness.